Vegetation history and human activity during the last 6000 years on the central Catalan coast (northeastern Iberian Peninsula) - Riera-Mora, S; Esteban-Amat, A (Vegetation History and Archaeobotany, 1994)
In this paper, we present the results of four pollen diagrams obtained from the northeastern coast of the Iberian Peninsula. These data, together with a set of 11 radiocarbon dates, allow us to make some suggestions about human activity in this area mainly during the last 6000 years. We have established four main stages of this activity. Phase I (7000-3000 B.P.) shows some sporadic human clearance without qualitative and/or quantitative changes inside the natural woodland, except for slight oscillations in AP values. These clearances are synchro- nous with Neolithic and Bronze Age settlements. Phase II (3000-1500/1300 B.P.) demonstrates a different hu- man action on the landscape along the Catalan coast. Sampling sites located in rich agricultural plains and close to urban centres show continuous woodland clear- ance during the Iberian period and especially during Ro- man times. In contrast, at boring sites far from these towns, the irregular and sporadic woodland disturbances continue, although these become more common. Phase III (1500/1300-850 B.P.) shows further woodland clear- ance fires along the coast. Pollen, archaeological and historical evidence allow us to relate this to the introduc- tion of grazing in the coastal area, connected with sea- sonal transhumance between the littoral and mountain regions. Phase IV (850-300/150 B.P.) is characterised by the final clearance of woodland and the development of olive farming. During this phase the agrarian Mediterra- nean landscape was definitively formed.
Keywords: Fires; Human disturbances; northeast Iberian Peninsula; olive; Seasonal transhumance

PYROLYSIS OF HOLM OAK AND OLIVE WOOD - Figueiredo, J L (International Conference on Biomass for Energy and Industry, 1989)
The pyrolysis of olive and holm-oak wood to produce charcoal and fuel gas was studied in the temperature range from 3 00 to 9 00°C. The charcoals were characterized by proximate and ultimate analyses, and the gases were analyzed chromatographycally The fised carbon content of the charcoal increased with temperature up to 600-700°C and then remained essentially constant. The gases produced were mainly CO, CO , H and CH . The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is 600'C.
APS
Keywords: charcoal production; fuel gas; Holm oak; olive; pyrolysis